Prioritized norms in formal argumentation. (20th March 2018) - Liao, Beishui; Oren, Nir; van der Torre, Leendert; Villata, Serena
Abstract: To resolve conflicts amongst norms, various non-monotonic formalisms can be used to perform prioritized normative reasoning. Meanwhile, formal argumentation provides a way to represent non-monotonic logics. In this paper we propose a representation of prioritized normative reasoning by argumentation. Using hierarchical abstract normative systems (HANS), we define three kinds of prioritized normative reasoning approaches called Greedy, Reduction and Optimization. Then, after formulating an argumentation theory for a HANS, we show that for a totally ordered HANS, Greedy and Reduction can be represented in argumentation by applying the weakest link and the last link principles, respectively, and Optimization can be represented by introducing additional defeats capturing the idea that for each argument that contains a norm not belonging to the maximal obeyable set then this argument should be rejected.